Hyperhomocysteinemia And Atherosclerosis – An Overveiw - V.GOVINDARAJU,; HARISH RAO, (International Journal of Pharma and Bio Sciences, 2011)
Indians are reported to have a very high prevalence of premature Coronary artery disease (CAD). A link between plasma homocysteine concentrations with vascular disease was first suggested by the observation made in patients with homocystinuria having arteriosclerosis. The recent interest in this topic has been generated by the evidence, that people with hyperhomocysteinemia have an increased risk of cardiovascular disease (CAD). On the basis of retrospective and epidemiological studies it is now widely accepted that hyperhomocysteienemia as an independent risk factor for cardiovascular disease. Present article gives an overview of the structural features, physiological significance and clinical implications of homocysteine with vascular disease.